Producing a Generation of Character: Transforming Responsibility, Discipline, and Society Through Tapak Suci in Primary Schools - Moch Safi’i; Romelah; Dina Mardiana (Al-Qalam Institute, 2024)
This study investigates the role of Tapak Suci, an extracurricular martial arts program, in shaping the character of students at MI Muhammadiyah 4 Kandat. The primary focus of the research is on how Tapak Suci contributes to the development of responsibility, discipline, and social character among students, addressing the growing concern over character education in schools. Using a qualitative case study approach, the research employed in-depth interviews, participant observation, and document analysis to collect data from the head of the school, Tapak Suci trainers, and students. The findings reveal that Tapak Suci activities promote responsibility through punctuality and adherence to training rules, discipline through structured routines, and social character through collaborative exercises. These findings highlight the potential of physical activities, particularly those with a moral and religious foundation, in fostering well-rounded character development in students. The study suggests that Tapak Suci can serve as a model for other schools aiming to integrate character education into extracurricular programs. The results also open avenues for future research on the long-term impact of martial arts-based character education across various educational contexts.